Inclusive climates and employee voice behavior: the roles of voice efficacy and voice channel design - Shen, Weiyi; Shen, Lidan (Frontiers in Psychology, 2025)
IntroductionEmployee voice serves as a critical source of organizational competitiveness. Scholars have discussed how to enhance employees' willingness to engage in voice behavior from multiple perspectives. But few studies have investigated the impact of voice channel design practices on employees' voice behavior. Based on sense-making theory, this study examined the effect of the organizational climate of inclusivity on voice behavior, with voice efficacy as a mediator and satisfaction with the design of voice channels as a moderator.MethodsUsing data collected from a sample of 281 university employees in eastern China, we analyzed a moderated mediation model.ResultsThe empirical results showed a significant relationship between an inclusive work climate and voice behavior. Voice efficacy played a partial mediation role in the relationship between an inclusive climate and voice behavior. Satisfaction with the design of voice channels positively moderated the positive effect of a climate for inclusion on voice behavior through voice efficacy. The moderating effect of satisfaction with a formal voice channel was more significant than that of satisfaction with an informal voice channel.DiscussionThe findings in this study may inform ways of motivating employees to proactively voice their opinions to promote the development of their organization. By fostering an inclusive organizational climate and designing effective voice mechanisms, organizations can strengthen employees' confidence in their capacity to make meaningful contributions, thereby elucidating how prior voice experiences influence subsequent voice-related decisions.